Determination of Multi-Class Antimicrobial Residues and Antimicrobial Resistance in Cow Milk and Feces Samples during Withdrawal Period - Hajrulai musliu, Zehra; Uzunov, Risto; Krluku, Maksud; Jovanov, Stefan; Stojkovski, Velimir; Arapcheska, Mila; Musliu, Dea; Sasanya, James Jacob (MDPI, 2023)
The use of antimicrobials in livestock production and their effect on the development of antimicrobial resistance (AMR) is a global health problem for humans, animals and the environment. The aim of this study was to determine antimicrobial residue levels in milk and feces samples during the withdrawal period in dairy cattle administrated with a single dose of the drug, as well as to characterize the antimicrobial resistance patterns of Escherichia coli cultured from feces samples. In the study, dairy cows from three different farms in North Macedonia were included. Raw milk and feces samples were collected before drug administration (0 day) and on the 1st, 2nd, 3rd, 7th and 21st day after drug administration. The antimicrobial residues of oxytetracycline, enrofloxacin, amoxicillin, trimethoprim and procaine-benzylpenicillin were determined using a validated liquid chromatography combined with tandem mass spectrometry (LC-MS/MS) method involving stable isotopes. According to results obtained, the highest levels of analyzed antimicrobial residues were determined on the first day after drug administration, which then gradually decreased until their elimination (7th day). The highest AMR of E. coli (100%) was found in β-lactam antimicrobials. Less exposure to broad-spectrum antimicrobials could be an important factor for reduction of AMR on dairy farms.
Keywords: antibiotic residues; antimicrobial resistance; LC-MS/MS; withdrawal period; milk; feces